Experiences of quality of life in people with Multiple Sclerosis who are in a wheelchair - Stine Torp Løkkeberg; Gunnar Thoresen (Wiley, 2022)
Abstract Aim The study includes health‐related quality of life for people in Norway with multiple sclerosis who live at home and are in a wheelchair (N = 6). The purpose is to show how they experience living with a chronic disease such as MS and how they perceive their own situation. How they value their own health and what leads to positive consequences is central to this study. Design The study has a qualitative design to show what health‐related experiences they had while living with MS. Method The interviews were conducted in their home and later transcribed. An interview guide with open‐ended questions was used. The transcribed material was analysed with a thematic analysis. Results Key themes were being free and independent, threat to the self and one's identity, and adaptation to MS. Free and independent in everyday life was essential for all the informants. Being dependent on others for basic needs was something they sought to avoid. Adapting to the new situation of changing roles was a challenge that required a lot of them.